Smart card : usability, transaction and problem at UiTM cafeteria (E-Cafe) / Siti Aishah Sahir - Sahir, Siti Aishah (2006)
The appearance of smart card technology that offers several advantages for many applications areas including educational institutions. The numerous numbers of universities and colleges adopted this technology in order to support multiple requirements and functions especially for students on a single card. This card provide flexibility to those students in order to access all facilities provided for them, identification purposes as well as acts as an electronic wallet systems. Since this card can store personal data about the cardholders, it also mainly used to store monetary value and used by the cardholders to make any transactions that relates to the money store on that card. The aims for this research are to determine the usability of this card as a medium for payment transactions used for UiTM electronic cafe (e-cafe) system, identify rate of transaction involves during payment process and also problems exists for this smart card implementation among students for e-cafe transactions. Primary and secondary data was used for collection the data in order to develop TAM theoretical framework and hypothesis for this research. Correlation coefficient analyses result shows there is significant relationship between perceived usefulness (PU) and perceived ease of use (PEOU) for e-cafe application. Although only two factors have significant relationship, other factors are having positive relationships among each of variables. Cross-tabulation analysis indicates that transaction rate has significant relationship with perceived usefulness. The outcomes from this research will suggest recommendations in order to support these implementations. Further the growth of electronic transactions will requires some understanding of the nature and capabilities of smart cards especially for students.